2019
DOI: 10.1155/2019/6724903
|View full text |Cite
|
Sign up to set email alerts
|

M2 Macrophages as a Potential Target for Antiatherosclerosis Treatment

Abstract: Atherosclerosis is a chronic progressive inflammation course, which could induce life-threatening diseases such as stroke and myocardial infarction. Optimal medical treatments for atherosclerotic risk factors with current antihypertensive and lipid-lowering drugs (for example, statins) are widely used in clinical practice. However, many patients with established disease still continue to have recurrent cardiovascular events in spite of treatment with a state-of-the-art therapy. Atherosclerotic cardiovascular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 174 publications
0
100
0
Order By: Relevance
“…In past decades, research on antiatherosclerosis drugs mainly focused on lipid-reducing, anti-inflammatory, and antioxidative strategies, endothelial protection and foam cell inhibition. Few studies have focused on macrophage polarization, which is also a promising target for atherosclerosis therapy [37,38]. Generally, the anti-inflammatory macrophage phenotype is considered atheroprotective, although CD163 + macrophages promote atherosclerosis [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…In past decades, research on antiatherosclerosis drugs mainly focused on lipid-reducing, anti-inflammatory, and antioxidative strategies, endothelial protection and foam cell inhibition. Few studies have focused on macrophage polarization, which is also a promising target for atherosclerosis therapy [37,38]. Generally, the anti-inflammatory macrophage phenotype is considered atheroprotective, although CD163 + macrophages promote atherosclerosis [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Both of these populations are plastic cells because they can switch from the M1 to M2 state and vice versa upon specific signals; the changes from M1 to M2 has been defined as "macrophage polarization" [28]. Furthermore, M1 macrophages exhibit elevated lipid accumulation, which contribute to the acceleration of atherosclerosis; whereas in contrast, M2 macrophages are located far from the lipid core of the plaque, contain smaller lipid droplets, and are involved in phagocytosis [29][30][31]. In particular, Chinetti et al showed that in the adventitia, M2 macrophages are twofold to threefold more abundant than M1 macrophages [29].…”
Section: Discussionmentioning
confidence: 99%
“…The opposite strategy of forcing macrophages into M2 phenotypes may be applied for the treatment of atherosclerosis [ 28 ]. LAIR1 (CD305) is an inhibitory collagen receptor expressed by certain blood cells, e.g., by monocytes.…”
Section: Macrophages As Perfect Cells For Reprogrammingmentioning
confidence: 99%